Strengthening the Family for Quality and Sustainable Livelihood - C. N., Oguonu (Journal of Home Economics Research, 2024)
This paper explores the possibilities of strengthening the family for sustainable livelihood. The paper adopts the multidisciplinary approach to deal with the multi-headed and multifaceted problems of the modern family. Using documentary data, this paper argued that the modern family is faced with enormous challenges and these challenges must be counteracted if family members should live sustainably. Some of the strategies for counteracting the family challenges were highlighted. The paper also advances strategies to minimize extensive food importation in most African countries.